A scrutiny of the MP-LADS in India: who is it for? - Pal, Rupayan; Das, Alparajita (2010)
This paper attempts to analyse the pattern and determinants of fund utilisation under the Members of Parliament-Local Area Development Scheme by the Lok Sabha MPS. It indicates that there are political business cycles in spending by MPS. Moreover, it shows that the degree of competition faced by an MP in the last election, his/her age, and political affiliation significantly affect fund utilisation. It also concludes that a higher level of awareness of general citizens and better law and order conditions in states restrict the MPS from misusing funds to gain political mileage. - Reproduced.
Keywords: Parliament; Local government